2019
DOI: 10.1001/jamadermatol.2018.5595
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cutaneous Squamous Cell Carcinoma in Immunosuppressed vs Immunocompetent Patients

Abstract: Discussion | Patients with HS have malignant lymphomas more frequently than the general population. Rates of NHL, HL, and CTCL in the general population are low. However, patients with HS appear to have 2 to 4 times the overall risk of developing lymphomas.Overall and subgroup associations between HS and lymphoma subtypes have not been evaluated previously in a population. A single-center retrospective series identified 1776 patients with HS in whom frequency of unspecified lymphoma was 1.8%. 5 In a Swedish r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…The heterogeneity of HNSCC in part is derived from molecular changes of the parenchyma ( 1 ), but also from the intricate and versatile tumor microenvironment ( 14 , 15 ). In squamous cell carcinomas, the incidence is lower in immunocompetent patients ( 16 ), and low immune infiltration has been shown to associate with a poor prognosis ( 17 ). Noteworthy, cancer patients with prospering immune responses are more likely to benefit from immune therapy ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of HNSCC in part is derived from molecular changes of the parenchyma ( 1 ), but also from the intricate and versatile tumor microenvironment ( 14 , 15 ). In squamous cell carcinomas, the incidence is lower in immunocompetent patients ( 16 ), and low immune infiltration has been shown to associate with a poor prognosis ( 17 ). Noteworthy, cancer patients with prospering immune responses are more likely to benefit from immune therapy ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fitting with the well-established observation that the incidence of squamous cell carcinomas is higher in immunocompromised patients (Herman et al 2007;Gonzalez et al 2019), the alleviation of cancer-potentiated immune suppression has shown potential in reducing HNSCC tumor burden and improving patient quality of life (Ferris et al 2016;Ferris et al 2018;Cohen et al 2019). The success of monoclonal antibodies blocking immune checkpoint receptor (ICR) signaling has transformed the landscape of emerging cancer therapeutic pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Besides signifying the sheer tumour burden in affected lung transplant recipients, multiple skin cancers have prognostic significance, as immunosuppressed patients with multiple SCCs appear to have poorer outcomes than those with single tumours. 12 It is therefore clinically important to address these gaps in knowledge about multiple skin cancers in transplant recipients. In a population-based cohort of lung transplant recipients, we estimated the age-standardized incidence rates of SCC and BCC in terms of persons affected and multiplicity of tumours, and we examined the associations between potential risk factors and multiple SCCs and BCCs.…”
mentioning
confidence: 99%
“…Besides signifying the sheer tumour burden in affected lung transplant recipients, multiple skin cancers have prognostic significance, as immunosuppressed patients with multiple SCCs appear to have poorer outcomes than those with single tumours . It is therefore clinically important to address these gaps in knowledge about multiple skin cancers in transplant recipients.…”
mentioning
confidence: 99%